ANALYSIS OF THE CURRENT STATE OF THE REGIONS OF THE REPUBLIC OF UZBEKISTAN - Tairovna, Abdalova Zulkhumor; Z.N, Tojiyeva. Z.N; Kaharovna, Tashtayeva Saida; Mamanazarovna, Egamberdiyeva Matluba; Leonidovich, Yanchuk Sergey (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the study of the territorial state of the national economy of the republic of uzbekistan, analysis of the current state of the socio-economic development of the regions, the author identifies the features and factors under the influence of which the regions develop, the main directions of reducing the sharp differentiation of regional development, and also highlights the specifics of socio-economic development and priority directions of the development strategy of the regions of uzbekistan.